Perception and Barriers to Indoor Air Quality and Perceived Impact on Respiratory Health: An Assessment in Rural Honduras - Audrey Le; Gonzalo Bearman; Kakotan Sanogo; Michael P. Stevens (Advances in Public Health)
Objective. The aim of this study was to identify household-specific factors associated with respiratory symptoms and to study the perceived impact of indoor air pollution (IAP) as a health issue. Methods. An IRB-approved, voluntary, anonymous 23-item survey was conducted in Spanish at a medical outreach clinic in June 2012 and at the homes of survey respondents N=79. Comparative analyses were performed to investigate relationships between specific house characteristics and respiratory complaints. Results. Seventy-nine surveys were completed. Respiratory symptoms were frequently reported by survey respondents: 42% stated that smoke in their household caused them to have watery eyes, 42% reported household members with coughs within the past two weeks, and 25% stated that there were currently household members experiencing difficulty in breathing. Stove location and kitchen roof construction material were significantly associated with frequency of respiratory symptoms. The vast majority used firewood as their major fuel type. Most respondents indicated that neither indoor air quality was a problem nor did it affect their daily life. Conclusions. Respiratory complaints are common in Yoro, Honduras. Stove location and kitchen roof construction material were significantly associated with frequency of respiratory symptoms; this may have implications for efforts to improve respiratory health in the region.